2019
DOI: 10.1002/jper.18-0710
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal trauma inhibits osteoblast differentiation and bone formation through IKK‐NF‐κB signaling

Abstract: Background:Occlusal trauma is an important factor promoting bone loss caused by periodontal diseases. Although there are reports of traumatic force promoting bone resorption in periodontal diseases, no studies examining the inhibition of bone formation by traumatic force and the underlying mechanism have been reported. The aim of this study was to investigate the mechanism whereby traumatic force inhibits bone formation.Methods: MC3T3-E1 cells were induced to undergo osteogenic differentiation and subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
4
19
0
1
Order By: Relevance
“…Traumatic compressive stress has been reported to activate NF-B signaling pathway. 15,16 In our study, this finding was verified again ( Figure 4A). To determine the role of Dancr in the regulation of NF-B signaling pathway, cells were transfected with Dancr-siRNA and cultured with induction medium for 5 days.…”
Section: Traumatic Compressive Stress Indirectly Activated Nf-b Signasupporting
confidence: 85%
See 4 more Smart Citations
“…Traumatic compressive stress has been reported to activate NF-B signaling pathway. 15,16 In our study, this finding was verified again ( Figure 4A). To determine the role of Dancr in the regulation of NF-B signaling pathway, cells were transfected with Dancr-siRNA and cultured with induction medium for 5 days.…”
Section: Traumatic Compressive Stress Indirectly Activated Nf-b Signasupporting
confidence: 85%
“…31 And the P65/P50 dimer and I B complex are best understood as the main regulator of NF-B activation. 32,33 As shown in our previous studies 15,16 and current results, NF-B signaling could be activated by traumatic stress, as demonstrated by notably increased expression of p-p65 and p-I B . Our previous studies 15,16 have found that traumatic force inhibited osteoblast differentiation through NF-B signaling.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations